Rapid and sensitive on-site detection of PBoV G3 using an EsCas13d-based platform - Peng-fei Fu; Zhuo-wei Zhang; Jun Hong; An-xin Hu; Yi-yang Shi; Jia-wen Lin; Si-yi Pi; Yu-yan Zhang; Yan-hong Wang; Min Lu; Guo-you Yin; Dong-mei Wang (Analytica Chimica Acta, 2026)

Closed-loop photothermal extraction and catalytic degradation for remediation of phenol-contaminated soil - Jian Zhang; Huimin Yu; Xiong Yang; Yafei Shi; Yi Lu; Gary Owens; Tiantian Deng; Kewu Pi; Pan Wu (Journal of Hazardous Materials, 2026)

Climatic drivers of vector-borne diseases: A nationwide causal inference study in China - Xu Wang; Jiayi Zhou; Jingtian Liu; Ying Liang; Fei Lu; Linjing Zhang; Yunchong Yao; Xinyue Fang; Yangchun Zheng; Xiaobo Liu; Zhong Hu; Qingying Zhang; et al. (Environmental Research, 2026)

Atomically dispersed Ruδ+-Ov-Ce3+ interfaces enable photothermal synergy-driven dry reforming of methane via a CH3O⁎ intermediate-mediated pathway - Fei Wang; Shule Liu; Jianfeng Lu; Jing Ding; Jing Xiao; Yunhong Pi; Weilong Wang (Chemical Engineering Journal, 2026)

Experimental and multiscale study on the mechanism of SO3 removal in pectin-modified chemical agglomeration - Lei Zhou; Manyun Xu; Huyuan Lu; Yiren Pi; Fengbin Ji; Zhe Liu; Zhiling Wang; Heng Chen (Chemical Engineering Journal, 2026)

Changes of soil nematode communities affect the soil labile phosphorus under nitrogen addition in Pinus taiwanensis forests - Chenxing Lian; Qiufang Zhang; Xiaoqing Zhang; Mengli Liu; Quanxin Zeng; Yaping Lin; Jiaohong Lu; Hao Sun; Huizhi Pi; Mengxiao Ren; Xiaochun Yuan; Juyan Cui; et al. (Applied Soil Ecology, 2026)

Soft sensing of NOx emissions in municipal solid waste incineration using a CBAM–CNN–Transformer model - Wenjing Li; Zhenghui Li; Anli Zhou; Wen Liu; Jianghong Chen; Wenbo Pi; Zhimin Lu; Shunchun Yao (Waste Disposal & Sustainable Energy, 2026)

Optimizing an anaerobic/aerobic/anoxic process by intermittent aeration and magnetic-activated-carbon-assisted aerobic sludge granulation for improved nitrogen and phosphorus removal - Yunsong Fang; Wenjie Liu; Kun Xin; Liu Pi; Zhenbao Wang; Likun Zhao; Hua Zhu; Yanjuan Lu; Jinyu Chen; Xuhui Mao (Journal of Water Process Engineering, 2026)

Methane biogeochemical turnover constrains arsenic transformation in groundwater systems: Organic molecular signatures and microbial functional networks - Xianjun Xie; Enyu Li; Honglin Jiang; Kunfu Pi; Lu Yan; Shuai Shen (Water Research, 2026)

Dual-path synergistic mechanism of coal spontaneous combustion based on the multi-scale characterization of the activation energy - Yong Chen; Yulong Zhang; Yu-long Zhang; Pi Lu; Junfeng Wang; Chunshan Zhou (Fuel, 2026)

Hydrogeochemical characteristics and the monitoring from 2020 to 2023 of hot spring waters in Tatun Volcanic Group, Taiwan - Ju-lien Pi; Hsueh-Yu Lu; Hsiao-Fen Lee; Hung-Chun Chao; Chen-Feng You; Tsung-Ren Peng; Raymond Patrick R. Maximo; Chia-Tai Wu; Ya-Wen Wu; Chung Fang; Cheng-Horng Lin (Journal of Asian Earth Sciences, 2025)

Analogical prediction of chiral-regulated self-assembling hydrogel guided by computational chemistry and molecular similarity principles to enhance wound healing - Xinru Tan; Jihui Lu; Yihang Zhao; Yiqing Huang; Wenmin Pi; Shuchang Yao; Liuyang Zhang; Jichang Wei; Zhiwei Wang; Xuemei Huang; Jia Zhang; Gangsheng Li; et al. (Chemical Engineering Journal, 2025)

Composition and contribution of disinfection by-product precursors in dissolved organic matter leached from aquatic plant residues - Jiachang Pi; Tingting Gong; Lei Gao; Xin Li; Yongze Lu; Hongyang Wang; Guangcan Zhu (Journal of Environmental Chemical Engineering, 2025)

Nondestructive classification of internal defects in camellia seeds and chestnuts using X-ray imaging: optimization and comparison of deep learning classifiers - Menglong Ma; Haitao Fu; Yixiao Wang; Zelin Lu; Ziwei Wang; Jingjing Cheng; Xiaodan Liu; Huang Dai; Fuwei Pi; Jiahua Wang (Food Control, 2025)

Multimetallic intra-nanogap nanozyme-mediated lateral flow immunoassay for ultrasensitive and multimode detection of K. pneumonia in clinical samples - Weixia Zhi; Xinjie Guo; Yichu Nie; Lu Nie; Tingting He; Li Dai; Jing Xu; Xiangxin Zong; Jun Xu; Huaihong Cai; Yong Tang; Yanguang Cong; et al. (Chemical Engineering Journal, 2025)

Protective effect of A-type ECG dimer on oxidative damage of retinal pigment epithelial cell - Xia Pi; Yuhan Lu; Yunfei Huang; Lanzhen Ban; Jiawei Bao; Chunmei Li (Food Bioscience, 2025)

Enhanced coagulation of Microcystis aeruginosa using titanium xerogel coagulant - Shulian Wang; Yanqun Li; Lu Cai; Xian Yang; Kewu Pi; Zhu Li (Chemosphere, 2025)

An HRP-integrated CRISPR/Cas12a biosensor towards chair-side diagnosis for Porphyromonas gingivalis - Ningning Pi; Rong Xiang; Lu Zhu; Yi Li; Xuan Wu (Biotechnology Letters, 2025)

Restoring sweat gland function in mice using regenerative sweat gland cells derived from chemically reprogrammed human epidermal keratinocytes - Jiangbing Xiang; Huating Chen; Hongliang Zhang; Lu Wu; Yan Li; Shuaifei Ji; Wei Pi; Shaoyuan Cui; Lei Dong; Xiaobing Fu; Xiaoyan Sun (Science Bulletin, 2024)

Quinclorac-resistant Echinochloa spp. promoted growth and reproduction of Laodelphax striatellus (Hemiptera: Delphacidae) probably by providing more nutrients and stable environment - Yimeng Pi; Yanhui Lu; Xia Yang; Wujia Mo; Qiang Li; Zhongxian Lu; Yongfeng Li; Yipeng Xu; Hongxing Xu (Pesticide Biochemistry and Physiology, 2024)

Bacterial mercury methylation modulated by vitamin B9: An overlooked pathway leads to increased environmental risks - Fang Fang; Lingyun Ding; Yaoyu Zhang; Xuejiao Qiao; Lu Qian; Ruqian Wei; Hanchun Chen; Haodong Ji; Bin Pi; Ming Hung Wong; Huchun Tao; Nan Xu; et al. (Journal of Hazardous Materials, 2024)

Natural diterpene carrier-free hydrogel enhances antigen presentation and intensifies T cell activation for tumor immunotherapy - Xiang Zhang; Luping Yang; Wenmin Pi; Linying Wu; Yisong Shu; Yihang Zhao; Shan Lu; Bo Wang; Jihui Lu; Zhijia Wang; Yaozhi Zhang; Shuchang Yao; et al. (Chemical Engineering Journal, 2024)

A low-carbon dual-functional evaporator with photothermal and catalytic properties for enhanced VOCs removal during water evaporation - Chen Shi; Pan Wu; Qianyun Xu; Qiao Ruan; Yi Lu; Xiong Yang; Yafei Shi; Gary Owens; Kewu Pi (Chemical Engineering Journal, 2024)

Anti-obesity effect of fucoidan from Laminaria japonica and its hydrothermal degradation product - Hai-Yan Lu; Xue Zhao; Tong-Jie Liu; Xi Liang; Mao-Zhen Zhao; Xiao-Ying Tian; Hua-Xi Yi; Pi-Min Gong; Kai Lin; Zhe Zhang; Lan-Wei Zhang (Food Bioscience, 2024)

Non-destructive detection and grading of chilling injury-induced lignification of kiwifruit using X-ray computer tomography and machine learning - Jiahua Wang; Yuqing Lin; Qiaocong Li; Zelin Lu; Jiangjin Qian; Huang Dai; Fuwei Pi; Xiaodan Liu; Yong He (Computers and Electronics in Agriculture, 2024)

Arsenic biogeochemical cycling association with basin-scale dynamics of microbial functionality and organic matter molecular composition - Xianjun Xie; Lu Yan; Shige Sun; Kunfu Pi; Jianbo Shi; Yanxin Wang (Water Research, 2024)

Long-term cadmium exposure induces epithelial-mesenchymal transition in breast cancer cells by activating CYP1B1-mediated glutamine metabolic reprogramming in BT474 cells and MMTV-Erbb2 mice - Jingdian Li; Peng Gao; Mingke Qin; Junhua Wang; Yan Luo; Ping Deng; Rongrong Hao; Lei Zhang; Mindi He; Chunhai Chen; Yonghui Lu; Qinlong Ma; et al. (Science of The Total Environment, 2024)

The role of mineral resources, sustainable finance, and innovation in promoting sustainable development under the IRA 2022 - Xiao-Guang Yue; Changyi Lu; Saiqi Pi; Hongyu Huang; Otilia Manta (Resources Policy, 2024)

Composite aerogel incorporating low temperature phase change microcapsules for enhanced thermal insulation - Bin Yan; Min Li; Honglang Lu; Menghan Pi; Jiahao Mu; Wei Cui; Rong Ran (Chemical Engineering Journal, 2024)

Bacterial, short-chain fatty acid and gas profiles of partially hydrolyzed guar gum in vitro fermentation by human fecal microbiota - Xiong-E Pi; Hao Fu; Xiao-Xia Yang; Zai-Chun Yu; Wei-Lin Teng; Yinjun Zhang; Xue-Wei Ye; Hui Hui Quan; Li-Zhi Lu; Wei Liu (Food Chemistry, 2024)

Experimental and numerical investigations on seismic responses of wind turbine structures with amplifying damping transfer system - Pi-Guang Wang; Hai-Qiang Lu; Meng Wang; Satish Nagarajaiah; Xiu-Li Du (Soil Dynamics and Earthquake Engineering, 2023)

Chronic cadmium exposure triggered ferroptosis by perturbing the STEAP3-mediated glutathione redox balance linked to altered metabolomic signatures in humans - Ping Deng; Jingdian Li; Yonghui Lu; Rongrong Hao; Mindi He; Min Li; Miduo Tan; Peng Gao; Liting Wang; Huihui Hong; Jiawen Tao; Muxue Lu; et al. (Science of The Total Environment, 2023)

Systematical Evaluation of the Structure-Cardiotoxicity Relationship of 7-Azaindazole-based PI3K Inhibitors Designed by Bioisosteric Approach - Tianze Wu; Yi Chen; Chengbin Yang; Mingzhu Lu; Fang Geng; Jianhua Guo; Yan Pi; Yun Ling; Jun Xu; Tong Cai; Lei Lu; Yaming Zhou (Cardiovascular Toxicology, 2023)

Hydrogel-based intelligent greenhouse films for simultaneous fogging prevention and indoor environmental monitoring - Honglang Lu; Huanxiong Liang; Jianle Liu; Hui Zhou; Menghan Pi; Min Li; Bin Yan; Wei Li; Wei Cui; Rong Ran (Chemical Engineering Journal, 2023)

NanoSIMS U–Pb dating of hydrothermally altered monazite: constraints on the timing of the Laozhaiwan Carlin-type gold deposit - PaiLong Luo; QiaoHui Pi; ZhiWen Lu (Arabian Journal of Geosciences, 2023)

Solar-Driven interfacial evaporation for decentralized direct potable reuse of domestic wastewater - Weixiang Chao; Shanshan Pi; Yang Yang; Zhida Li; Yongjie Yu; Ying Yang; Ruijie Yang; Haiyan Li; Lu Lu (Chemical Engineering Journal, 2023)

Elevated Interleukin-37 Associated with Dengue Viral Load in Patients with Dengue Fever - Jun-Ai Zhang; Jia-Jun Wang; Wen-Ting Zhang; Li Zhang; Bi-Ying Zheng; Gan-Bin Liu; Jing Liang; Yuan-Bin Lu; Xian-Jin Wu; Shu-Ying Yao; Guo-Ying Chen; Yun-Qi Xie; et al. (Current Microbiology, 2023)
Dengue remains a public health issue worldwide. Similar to chronic infectious diseases, stimulation of cytokine production is not enough to drive immune effector cells for effective virus clearance. One possible mechanism is the virus induces a large number of negative stimulatory cytokines inhibiting immune response. Interleukin 37 (IL-37) plays a crucial regulatory role in infection and immunity, inhibits innate and adaptive immunity as an anti-inflammatory cytokine by inhibiting proinflammatory mediators and pathways. To date, there are few studies reporting correlations between dengue fever (DF) and IL-37. In this study we found that the serum IL-37b and IL-37b-producing monocytes in patients were significantly increased in DF patients. A majority of the IL-37b produced by DF patients was produced by monocytes, not lymphocytes. Increased levels of IL-6, IL-10, and IFN-α were also found in DF patients. However, we failed to detect IL-1β, IL-17A and TNF-α in plasma, because of off-target. In our study, there was no relation between IL-6, IL-10, and IFN-α expressions and IL-37b in serum ( P > 0.05). The IL-37b-producing monocytes were negatively correlated with the level of IFN-α in serum and platelet count, and positively correlated with lymphocytes percentage ( P < 0.05, respectively). Additionally, serum DENV nonstructural protein 1 levels were positively correlated with monocytes percentages ( P < 0.05). Our data represents findings for IL-37b expression and its potential mechanisms in DF patients’ immune response.

Non-destructive determination of internal defects in chestnut (Castanea mollissima) during postharvest storage using X-ray computed tomography - Jiahua Wang; Zelin Lu; Xiaofeng Xiao; Mengting Xu; Yuqing Lin; Huang Dai; Xiaodan Liu; Fuwei Pi; Donghai Han (Postharvest Biology and Technology, 2023)

The distribution, behavior, and release of macro- and micro-size plastic wastes in solid waste disposal sites - Xunchang Fei; Hongping He; Xiaoqing Pi; Xuhong Lu; Qinqin Chen; Jun Ma; Yao Wang; Mingliang Fang; Chuangzhou Wu; Shijin Feng (Critical Reviews in Environmental Science and Technology, 2023)

Adaptability of organic matter and solid content to Fe2+/persulfate and skeleton builder conditioner for waste activated sludge dewatering - Xiaoran Li; Yafei Shi; Xi Zhou; Lu Wang; Huiqin Zhang; Kewu Pi; Andrea R. Gerson; Defu Liu (Environmental Science and Pollution Research, 2022)

A comparison of atmospheric geochemistry through lichens from volcanic and non-volcanic areas, north Taiwan - Le-Qi Lin; Hsueh-Yu Lu; Ju-Lien Pi; Tai-Sheng Liou; Wen-Fu Chen; Pei-Shan Hsieh (Journal of Earth System Science, 2021)

Talaromyces Marneffei Infection in an HIV-Negative Child with a CARD9 Mutation in China: A Case Report and Review of the Literature - Cheng-yan You; Fang Hu; Si-wei Lu; Dan-dan Pi; Feng Xu; Cheng-jun Liu; Yue-qiang Fu (Mycopathologia, 2021)

Assessing Thickness of Burn Scars Through Ultrasound Measurement for Patients with Arm Burns - Pi-Wen Huang; Chih-Wei Lu; Kwo-Ta Chu; Ming-Te Ho (Journal of Medical and Biological Engineering, 2021)

Influence of near-fault ground motion characteristics on the seismic response of cable-stayed bridges - Chao Zhang; Jian-bing Lu; Hong-yu Jia; Zhi-chao Lai; Xu Li; Pi-guang Wang (Bulletin of Earthquake Engineering, 2020)

Paleogeography of South China in the Early Paleozoic: evidence from U–Pb geochronology of detrital monazite - Xiong Yang; Qiaohui Pi; Di Lu; Huidong Yu (Arabian Journal of Geosciences, 2020)

Enhanced adsorption performance and regeneration of magnetic Fe3O4 nanoparticles assisted extracellular polymeric substances in sulfonamide-contaminated water - Shanshan Pi; Ang Li; Di Cui; Zhou Su; Lu Zhou; Fang Ma (Environmental Science and Pollution Research, 2020)

The effects of El Niño‐Southern Oscillation events on intertidal seagrass beds over a long‐term timescale - Hsing‐Juh Lin; Chen‐Lu Lee; Shang‐En Peng; Meng‐Chi Hung; Pi‐Jen Liu; Anderson B. Mayfield (Global Change Biology, 2018)
El Niño‐Southern Oscillation (ENSO) events can cause dramatic changes in marine communities. However, we know little as to how ENSO events affect tropical seagrass beds over decadal timescales. Therefore, a diverse array of seagrass ( Thalassia hemprichii ) habitat types were surveyed once every 3 months for 16 years (January 2001 to February 2017) in a tropical intertidal zone that is regularly affected by both ENSO events and anthropogenic nutrient enrichment. La Niña and El Niño events had distinct effects on the biomass and growth of T. hemprichii . During La Niña years, higher (a) precipitation levels and (b) seawater nitrogen concentrations led to increases in seagrass leaf productivity, canopy height, and biomass. However, the latter simultaneously stimulated the growth of periphyton on seagrass leaves; this led to decreases in seagrass cover and shoot density. More frequent La Niña events could, then, eventually lead to either a decline in intertidal seagrass beds or a shift to another, less drought‐resistant seagrass species in those regions already characterized by eutrophication due to local anthropogenic activity.

Trace Elements Characteristics of Black Shales from the Ediacaran Doushantuo Formation, Hubei Province, South China: Implications for Redox and Open vs. Restricted Basin Conditions - Bi Zhu; Shaoyong Jiang; Daohui Pi; Lu Ge; Jinghong Yang (Journal of Earth Science, 2018)

Concentrations and Exposure Evaluation of Metals in Diverse Food Items from Chengdu, China - Rong Wang; Bifeng Zhong; Lu Pi; Fuyu Xie; Mengqin Chen; Sanglan Ding; Shijun Su; Zhi Li; Zhiwei Gan (Archives of Environmental Contamination and Toxicology, 2018)

TRPV1 attenuates intracranial arteriole remodeling through inhibiting VSMC phenotypic modulation in hypertension - Ming-Jie Zhang; Yun Liu; Zi-Cheng Hu; Yi Zhou; Yan Pi; Lu Guo; Xu Wang; Xue Chen; Jing-Cheng Li; Li-Li Zhang (Histochemistry and Cell Biology, 2017)

The critical role of ABCG1 and PPARγ/LXRα signaling in TLR4 mediates inflammatory responses and lipid accumulation in vascular smooth muscle cells - Xiaojie Cao; Lili Zhang; Chunhai Chen; Qingsong Wang; Lu Guo; Qinlong Ma; Ping Deng; Gang Zhu; Binghu Li; Yan Pi; Chunyan Long; Lei Zhang; et al. (Cell and Tissue Research, 2017)

Concentrations and health risk assessment of metal(loid)s in indoor dust from two typical cities of China - Yiwen Li; Lu Pi; Wenli Hu; Mengqin Chen; Yan Luo; Zhi Li; Shijun Su; Zhiwei Gan; Sanglan Ding (Environmental Science and Pollution Research, 2016)

Grain Size Distribution and Health Risk Assessment of Metals in Outdoor Dust in Chengdu, Southwestern China - Mengqin Chen; Lu Pi; Yan Luo; Meng Geng; Wenli Hu; Zhi Li; Shijun Su; Zhiwei Gan; Sanglan Ding (Archives of Environmental Contamination and Toxicology, 2016)

Rapidly Dissolvable Microneedle Patches for Transdermal Delivery of Exenatide - Zhuangzhi Zhu; Huafei Luo; Wangding Lu; Hansen Luan; Yubo Wu; Jing Luo; Youjie Wang; Jiaxin Pi; Chee Yen Lim; Hao Wang (Pharmaceutical Research, 2014)

Amino Acid, Fatty Acid, and Metal Compositions in Edible Parts of Three Cultured Economic Crabs: Scylla paramamosain, Portunus trituberculatus , and Eriocheir sinensis - Ke-Ji Jiang; Feng-Ying Zhang; Yan Pi; Li-Li Jiang; Zhong-Li Yu; Dan Zhang; Man-Man Sun; Lu-Jiao Gao; Zhen-Guo Qiao; Ling-Bo Ma (Journal of Aquatic Food Product Technology, 2014)

Recent advances in 2D and 3D in vitro systems using primary hepatocytes, alternative hepatocyte sources and non-parenchymal liver cells and their use in investigating mechanisms of hepatotoxicity, cell signaling and ADME - Patricio Godoy; Nicola J. Hewitt; Ute Albrecht; Melvin E. Andersen; Nariman Ansari; Sudin Bhattacharya; Johannes Georg Bode; Jennifer Bolleyn; Christoph Borner; Jan Böttger; Albert Braeuning; Robert A. Budinsky; et al. (Archives of Toxicology, 2013)

Association between estrogen receptor alpha c.454-397T>C and c.454-351A>G and ischemic stroke risk: a systematic review and meta-analysis - Bing-Hu Li; Li-Li Zhang; Yan-Wei Yin; Yan Pi; Lu Guo; Qing-Wu Yang; Chang-Yue Gao; Chuan-Qin Fang; Jing-Zhou Wang; Jing Xiang; Jing-Cheng Li (Molecular Biology Reports, 2012)

Erratum to: Genetic variation in the carbonyl reductase 3 gene confers risk of type 2 diabetes and insulin resistance: a potential regulator of adipogenesis - Yi-Cheng Chang; Pi-Hua Liu; Yun-Chih Tsai; Yen-Feng Chiu; Shyang-Rong Shih; Low-Tone Ho; Wen-Jane Lee; Chieh-Hua Lu; Thomas Quertermous; J. David Curb; Wei-Jei Lee; Po-Chu Lee; et al. (Journal of Molecular Medicine, 2012)

Genetic variation in the carbonyl reductase 3 gene confers risk of type 2 diabetes and insulin resistance: a potential regulator of adipogenesis - Yi-Cheng Chang; Pi-Hua Liu; Yun-Chih Tsai; Yen-Feng Chiu; Shyang-Rong Shih; Low-Tone Ho; Wen-Jane Lee; Chieh-Hua Lu; Thomas Quertermous; J. David Curb; Wei-Jei Lee; Po-Chu Lee; et al. (Journal of Molecular Medicine, 2012)

Taxonomic treatments of Camellia (Theaceae) species with secretory structures based on integrated leaf characters - B. Jiang; Q. F. Peng; Z. G. Shen; M. Möller; E. X. Pi; H. F. Lu (Plant Systematics and Evolution, 2010)